Superconductivity in Undoped CaFe2As2 Single Crystals - 陈东云 于佳 阮彬彬 郭琦 张蕾 陈根富 任治安 (中国物理快报：英文版, 2016)
Single crystals of undoped CaFe2As2 are grown by an FeAs self-flux method, and the crystals are quenched in ice-water rapidly after high-temperature growth. The quenched crystal undergoes a collapsed tetragonal structural phase transition around 80 K revealed by the temperature-dependent x-ray diffraction measurements. Superconductivity below 25 K is observed in the collapsed phase by resistivity and magnetization measurements. The isothermal magnetization curve measured at 2 K indicates that this is a typical type-ll superconductor. For comparison, we systematically characterize the properties of the furnace-cooled, quenched, and post-annealed single crystals, and find strong internal crystallographic strain existing in the quenched samples, which is the key for the occurrence of superconductivity in the undoped CaFe2As2 single crystals.